2015
DOI: 10.4103/2229-516x.165382
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of skin grafts to postoperative radiotherapy

Abstract: Aim:The aim was to evaluate the integrity and functional outcomes of skin grafts following external beam radiotherapy (EBRT).Materials and Methods:A prospective study of 15 patients, in whom EBRT was planned after their wound coverage with split-thickness skin graft (STSG). Parameters evaluated include defect size, time to postoperative radiotherapy, total radiotherapy dose, delays and interruptions in radiotherapy, wound complications, and the need for further surgical interventions.Results:In all the 15 (6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…Artamanova et al also observed that full thickness skin grafts were associated with necrosis [1]. Lal et al reported no increased WHCs after radiation in skin grafts, but the study included only 15 patients and their median age was 52 years, while the median age in the present study was 77 years [27]. Bui et al also reported no increased occurrence of WHCs in split thickness skin grafts after irradiation [26].…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Artamanova et al also observed that full thickness skin grafts were associated with necrosis [1]. Lal et al reported no increased WHCs after radiation in skin grafts, but the study included only 15 patients and their median age was 52 years, while the median age in the present study was 77 years [27]. Bui et al also reported no increased occurrence of WHCs in split thickness skin grafts after irradiation [26].…”
Section: Discussionmentioning
confidence: 45%
“…Sumi et al discovered that the reaction of skin grafts on rats to irradiation depends on the time interval between the transplantation and radiotherapy [11,18,24,28,29]. Skin grafts that were irradiated in the early hypovascular stage (2 days) reacted mildly to moderately, those irradiated in the hypervascular stage (2 days -3 weeks) reacted severely and those irradiated in the late hypervascular stage (3-4 weeks) reacted similarly to normal skin [18,24,27,30]. They also showed a similar course for irradiated skin flaps, which reacted akin to normal skin in the late hypervascular stage (3-4 weeks) [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(21) The use of skin grafts for fault coverage in patients who received irradiation following neighbouring tissue transfer has provided satisfactory outcomes. (22) We observed in our study that 5 out of 7 had 100% graft taken following radiation therapy; graft failure was observed in only one patient. These findings show that in individuals with numerous disorders for whom protracted anesthesia is judged inadequate, Split thickness skin grafts are a safe choice for masking local abnormalities following scalp radiation therapy.…”
Section: Discussionmentioning
confidence: 46%
“…The treatment can be started as early as 3-4 weeks after skin grafting as long as the skin grafts are placed on well-vascularized healthy tissues. Minor skin graft loss due to radiotherapy can usually be treated conservatively 11 .…”
Section: Discussionmentioning
confidence: 99%